Islamic Khitbah (A Comparison of Madzhabs in Islam) - Shofiatul Khulqi, Salwa; Eva Novita Restu, Cut; Sucipto, Imam (PT ARRUS Intelektual Indonesia, 2023)
The importance of family in Islam is widely recognized, as it serves as the foundation for the construction of strong, resilient, harmonious, and happy societies. The establishment of a peaceful and cohesive society is intricately linked to the well-being of each family unit, as families are regarded as the epitome of a nation. To foster harmonious families, the adherence to appropriate processes and procedures in line with Islamic law and local customs is crucial. The dynamics and evolution of social traditions and customs in the context of premarital life exhibit diverse styles. For instance, the engagement traditions observed in various communities such as Seserahan in Java, Peningset or Ngemblok in Sunda, Merisik in Riau, Marhusip in Batak, Maminang in Minangkabau, Mapettuada in Bugis, and many others, exemplify the distinct premarital proposal customs prevalent in society. Khitbah refers to the formal request made by a man to a woman, or vice versa, expressing the intention to marry. It can be done directly or through intermediaries, in accordance with the provisions of Sharia. The Quranic evidence for Khitbah can be found in Surah Al-Baqarah (Chapter 2), Verse 235. Additionally, various hadiths discuss Khitbah, with one narrated by Abu Daud emphasizing the importance of motivating factors when proposing marriage.